Dampak Pengelolaan Desa Wisata Lantan terhadap Perubahan Ekonomi Masyarakat Desa Lantan, Kecamatan Batukeliang Utara, Kabupaten Lombok Tengah - Rizki, Zainul; Sahri, H.; Singandaru, Adhitya Bagus (Lembaga Yasin AlSys, 2026)
Lantan Tourism Village has developed as one of the drivers of the local economy with the potential to influence the community’s socio-economic structure through increased income, job creation, and the strengthening of community-based economic activities. This study aimed to determine the impact of the management of Lantan Tourism Village on socio-economic changes within the community and to contribute to development economics discourse as well as provide practical input for optimizing tourism village management to improve community welfare. A descriptive qualitative method with a case study approach was employed to understand the impact of tourism village management through the direct experiences of key actors. Data were collected through observation, in-depth interviews, and documentation, with informants comprising the village head and members of the tourism-awareness group (Pokdarwis), selected using purposive and snowball sampling techniques. Data analysis followed the Miles and Huberman model, including data collection, data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation techniques. The findings show that the management of Lantan Tourism Village based on community-based tourism (CBT) principles has significantly transformed the local economy and improved community welfare, as reflected in increased income, more diverse employment opportunities, and higher household consumption. This success is closely linked to active community participation, strong government support, and strategic collaboration among stakeholders that ensure a fairer and more sustainable distribution of tourism benefits. These findings underscore the importance of strengthening community capacity, improving supporting infrastructure, and optimizing tourism village promotion as prerequisites for the long-term sustainability of Lantan Tourism Village development.